ANALISA VARIASI LAMA FERMENTASI ISOLAT ACTINOMYCETES TERHADAP PERTUMBUHAN CANDIDA ALBICANS SECARA IN VITRO - Rizki Deby Wulandari (2022)
Actinomycetes are Gram Positive bacteria, rod-shaped, chain arrangement with branches that can produce bioactive compounds that have antifungal activity. Fungal infection in humans caused by Candida is candidiasis. C.albicans is the species that most often causes candidiasis. The aim of this study was to determine the effectiveness of Actinomycetes isolates in inhibiting the growth of C. albicans. This research was conducted in vitro with samples of Actinomycetes isolates obtained from Bogor Botanical Garden soil which were then isolated on growth media and brewed for 1, 2, and 3 days and then tested on C. albicans fungi using the well method. The results obtained from the three groups obtained an average inhibition zone of 8.84 mm; 9.64mm; 9.42mm. The results of the One-way Anova test with p = 0.000 showed that the average inhibition of C. albicans growth by Actinomycete isolates was significantly different. The bioactive compounds produced by Actinomycetes work by damaging the cell wall components and cell membranes of the C. albicans fungal.